Screening the maize rhizobiome for consortia that improve Azospirillum brasilense root colonization and plant growth outcomes - Barua, Niloy; Clouse, Kayla M.; Ruiz Diaz, Dorivar A.; Wagner, Maggie R.; Platt, Thomas G.; Hansen, Ryan R. (Frontiers in Sustainable Food Systems, 2023)
Plant growth-promoting bacteria (PGPB) are valuable for supporting sustainable food production and may alleviate the negative impacts of chemical fertilizers on human health and the environment. While single-strain inoculations have proven unreliable due to poor survival and colonization in the rhizosphere, application of PGPB in multispecies consortia has the potential to improve these outcomes. Here, we describe a new approach for screening and identifying bacterial consortia that improve the growth of corn relative to plants inoculated with a single strain. The method uses the microwell recovery array (MRA), a microfabricated high-throughput screening device, to rapidly explore the maize (Zea mays L.) rhizobiome for higher-order combinations of bacteria that promote the growth and colonization of the nitrogen-fixing PGPB, Azospirillum brasilense. The device simultaneously generates thousands of random, unique combinations of bacteria that include A. brasilense and members of the maize rhizobiome, then tracks A. brasilense growth in each combination during co-culture. Bacteria that show the highest levels of A. brasilense growth promotion are then recovered from the device using a patterned light extraction technique and are identified. With this approach, the screen uncovered growth-promoting consortia consisting primarily of bacteria from the Acinetobacter-Enterobacter-Serratia genera, which were then co-inoculated with A. brasilense on axenic maize seedlings that were monitored inside a plant growth chamber. Compared to maize plants inoculated with A. brasilense alone, plants that were co-inoculated with these consortia showed accelerated growth after 15 days. Follow-up root colonization assays revealed that A. brasilense colonized at higher levels on roots from the co-inoculated seedlings. These findings demonstrate a new method for rapid bioprospecting of root and soil communities for complementary PGPB and for developing multispecies consortia with potential use as next-generation biofertilizers.